2003
DOI: 10.1063/1.1617973
|View full text |Cite
|
Sign up to set email alerts
|

Multiconfigurational self-consistent field study of the silicon carbide (001) surface

Abstract: Multiconfigurational self-consistent field calculations have been performed to investigate structural and electronic properties of cubic siliconcarbide (001) (SiC (001)) surfaces. The dimer on silicon-terminated SiC (001) (Si-SiC (001)) is found to be diradical in nature, due to destabilization of the π bond by bending the dimer. Since the SiClattice constant is larger than that of diamond, the >C=C< dimer on the carbonterminated SiC (001) (C-SiC (001)) surface is flatter and its π bond is stronger than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 65 publications
1
25
0
Order By: Relevance
“…For performing QM/MM calculations, the SIMOMM (Surface Integrated Molecular Orbital/Molecular Mechanics) method [34] was used. This method was successfully applied to the study of different adsorbates on Si(100) [25,35,36], SiC(100) [37], and diamond (100) [19] surfaces. In the present work, it was employed to characterize the larger model system described in Section 2.1, C 292 H 120.…”
Section: Qm/mm Approachmentioning
confidence: 99%
“…For performing QM/MM calculations, the SIMOMM (Surface Integrated Molecular Orbital/Molecular Mechanics) method [34] was used. This method was successfully applied to the study of different adsorbates on Si(100) [25,35,36], SiC(100) [37], and diamond (100) [19] surfaces. In the present work, it was employed to characterize the larger model system described in Section 2.1, C 292 H 120.…”
Section: Qm/mm Approachmentioning
confidence: 99%
“…An important consideration in cycloaddition reactions such as those studied here is the possibility of their occurring through a radical mechanism. Multi-reference self consistent field cluster calculations of the SiC(001)-2x1 surface suggest that the topmost dimer exhibits significant diradical character (Tamura & Gordon, 2003), and since DFT is a single-reference method, multi-reference contributions are generally not included.…”
Section: Reactions On the 3c-sic(001)-3×2 Surfacementioning
confidence: 99%
“…The SIMOMM framework imposes a less rigid treatment of the capping atoms than its predecessor, the IMOMM model of Maseras and Morokuma [41], and this reduces artificial strain imposed on the QM structure. SIMOMM was originally developed for the study of surface chemical systems, and by now its utility has been demonstrated repeatedly for describing chemistry on Si and SiC surfaces [42][43][44][45][46][47][48][49][50][51]. SIMOMM geometry optimizations are perfomed under the Born-Oppenheimer approximation, which in this case is based on extremely robust assumptions [52].…”
Section: Introductionmentioning
confidence: 99%